WORKPLACE WELLBEING AND WORK ENGAGEMENT AMONG GENERATION Z EMPLOYEES IN PT X: THE ROLE OF PSYCHOLOGICAL CAPITAL AS A MODERATOR - Gozali, Vanesa Aprilia; Zamralita, Zamralita; Lie, Daniel (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2024)
This research aims to examine the role of psychological capital as a moderator in the relationship between workplace well-being and work engagement. Researchers used three measuring tools, namely: the Workplace Well-being Questionnaire (WWQ), the Utrecht Work Engagement Scale (UWES-9), and the Psychological Capital Questionnaire. The subjects in this research were employees from one of the manufacturing companies, namely PT X, and they totaled 144 participants. The method employed was non-experimental quantitative, utilizing convenience sampling (a non-probability sampling techniques) for data collection and employing Moderated Regression Analysis (MRA) for analysis. The results obtained by the researchers indicated that psychological capital plays a role in strengthening the relationship between well-being at work and work engagement. It is hoped that this research can help companies to facilitate, direct and improve work engagement.